ARTIFICIAL INTELLIGENCE AND PUBLIC SERVICES: PROSPECTS OF DIGITALIZATION IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the potential of Artificial Intelligence (AI) in transforming public services in Uzbekistan. It analyzes the current digitalization process, explores opportunities for enhancing efficiency, transparency, and accessibility, and identifies existing challenges. The paper highlights the importance of AI-based solutions for improving governance and accelerating national development.
Keywords: Artificial Intelligence, Digitalization, Public Services, Uzbekistan, E-government, Innovation, Transparency, Governance.